Dielectric relaxation in BaTiO3–Bi(ZnZr)O3 - Qian Wang; Jian-Hong Hu; Jun-Yi Liu; Chun-Ming Wang; Chun-Lei Wang (Journal of Advanced Dielectrics)
Dielectric relaxation behaviors of (1–x)BaTiO3–xBi(Zn[Formula: see text]Zr[Formula: see text]O3 (BT–BZZ, [Formula: see text]) have been analyzed at various temperatures. Both Havriliak–Negami (H–N) and Jurlewicz–Weron–Stanislavsky (J–W–S) relaxations are identified in these ceramic compositions. H–N relaxation happens in compositions with a small mole ratio of Bi(Zn[Formula: see text]Zr[Formula: see text]O3 (BZZ), while J–W–S type relaxation appears in compositions with a large mole ratio. Static dielectric constant, relaxation time and Jonscher indices are also obtained. The general trend of static dielectric constants decreases with increasing mole ratio of BZZ, while the relaxation time increases dramatically correspondingly. The low Jonscher index m is about 0.45 at low temperature for compositions with high mole ratio and increases with increasing of temperature. The high Jonscher index 1–n is around 0.1 at low temperature for compositions with high mole ratio and slightly decreases with increasing of temperature. Jonscher indices diagram with compositions of different mole ratios is plotted for easy identification of the relaxation types. Our results indicate that the relaxation behaviors in this BT–BZZ system show a strong deviation from the standard Debye model.